2016
DOI: 10.4103/1305-7456.184151
|View full text |Cite
|
Sign up to set email alerts
|

Chemomechanical caries removal method versus mechanical caries removal methods in clinical and community-based setting: A comparative in vivo study

Abstract: Objective:To compare the effectiveness of various caries removal techniques in mandibular primary molars using Smart Burs, atraumatic restorative technique (ART) (mechanical caries removal) and Carie-care (chemomechanical caries removal [CMCR]) among primary school children in clinical and community-based settings.Materials and Methods:A total of 80 carious primary mandibular molars were selected for the study from the dental clinic and community. They were equally assigned to four groups according to caries r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In the literature, the clinical application of Brix3000™ has been reported only in comparison with rotary instruments (Alkhouli et al 2020;Vila-Sierra et al 2019), but conventional methods of caries tissue removal are already associated with increased anxiety and fear in young patients. This occurs due to vibration and heat produced, which can migrate into the pulp, causing pain and a consequent negative experience (Kumar et al 2016). The ART technique, in contrast, is known as a method that reduces child discomfort (Leal .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the clinical application of Brix3000™ has been reported only in comparison with rotary instruments (Alkhouli et al 2020;Vila-Sierra et al 2019), but conventional methods of caries tissue removal are already associated with increased anxiety and fear in young patients. This occurs due to vibration and heat produced, which can migrate into the pulp, causing pain and a consequent negative experience (Kumar et al 2016). The ART technique, in contrast, is known as a method that reduces child discomfort (Leal .…”
Section: Discussionmentioning
confidence: 99%
“…Santosh Kumar KVK[ 20 ] reported working time of 7 and 6.66 min by using Carie Care in dental clinic and field setting, respectively, while smart bur consumed 5.85 min, which was significantly less than the Carie Care technique.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there was no statistically significant difference between preand post-treatment behaviors of the two groups. 19 Kumar et al 20 examined 80 baby molar teeth using the atraumatic restorative technique as well as chemomechanical caries removal methods, and reported that the chemo-mechanical method took a longer time, but it was more acceptable to pediatric patients.…”
Section: Discussionmentioning
confidence: 99%